Protoforms of information and communication activities during the reign of Vytautas (the second half of the XIV – early XV century) - Voyush, Inha D. (Journal of the Belarusian State University. Journalism, 2019)
The form of information and communication activities at the turn of the XIV and XV centuries on the territory of Belarus and their probable correlation with the modern practice of public relations are considered. The ways of giving socially significant content to Duke Vytautas activities and his identity during the reign, the exercise of internal and external contacts by the Grand Duchy of Lithuania are analysed as well as the positioning of the top person of the state through the external attributes of the princely court.